A Case Study of Early Experience with Implementation of Collaborative Care in the Veterans Health Administration - Tai–Seale, Ming (Mary Ann Liebert, Inc., 2010)
Primary care remains critically important for those who suffer from mental disorders. Although collaborative care, which integrates mental health services into primary care, has been shown to be more effective than usual care, its implementation has been slow and the experience of providers and patients with collaborative care is less well known. The objective of this case study was to examine the effects of collaborative care on patient and primary care provider (PCP) experiences and communication during clinical encounters. Participating physicians completed a self-administered visit reconstruction questionnaire in which they logged details of patient visits and described their perceptions of the visits and the influence of collaborative care. Audio recordings of visits were analyzed to assess the extent of discussion about colocated mental health services and visit time devoted to mental health topics. The main outcome measures were the extent of discussion and recommendation for collaborative care during clinical visits and providers' experiences based on their responses to the visit reconstruction questionnaire. Providers surveyed expressed enthusiasm about collaborative care and cited the time constraint of office visits and lack of specialty support as the main reasons for limiting their discussion of mental health topics with patients. Despite the availability of mental health providers at the same clinic, PCPs missed many opportunities to address mental health issues with their patients. Ongoing education for PCPs regarding how to conduct a “warm handoff” to colocated providers will need to be an integral part of the implementation of collaborative care. (Population Health Management 2010;13:331–337)